The Resilience of Junior High School Students in Online Learning in the New Normal Era - Widyastuti, Agnes; Ninin, Retno Hanggarani (Psikoborneo: Jurnal Ilmiah Psikologi, 2024)
The New Normal era post COVID-19 pandemic has an impact on the change of teaching learning system become online. Various kinds of challenges arise during online learning become adversity. The adversity of online learning made students stressed and put them at risk of academic failure, such repeated classes or dropping out. This situation may reduce the participation rate of compulsory education students, particularly in the secondary level. However, many studies have proven that students who are at risk of academic failure due to various factors of difficulty can succeed because they have a capacity called resilience. This research aims to explore and describe the resilience of students during online learning. This research uses a qualitative approach with secondary school’s students’ participants. A total of 4 students participated in this research and data was collected through online semi-structured interviews. The interview guide regarding resilience was developed from Reivich Shatte resilience theory. The interview results were analyzed based on themes. This research describes the resilience of secondary school’s students who doing online learning by 5 capacities of 7 aspects of resilience: emotion regulation, impulse control, causal analysis, empathy and reaching out in carrying out challenging online learning activities. However, the students still lack two other aspects which are realistic optimism and self-efficacy. The result of this research provides information to teachers in schools about the aspects of student which need to be improved aiming to make them resilient while doing online learning.Era Kebiasaan Baru (New Normal) paska pandemi COVID-19 berdampak pada perubahan cara belajar mengajar menjadi sistem pembelajaran jarak jauh secara daring. Berbagai macam tantangan dalam belajar daring muncul menjadi kesulitan. Kesulitan belajar daring dapat membuat murid stres dan berisiko gagal secara akademik, seperti tidak naik kelas bahkan putus sekolah. Keadaan tersebut dapat menurunkan angka partisipasi peserta didik wajib belajar terutama di tingkat SMP. Namun demikian, banyak studi yang membuktikan murid yang berisiko gagal secara akademik karena beragam faktor kesulitan dapat berhasil karena memiliki kapasitas yang disebut resiliensi. Penelitian ini bertujuan untuk mengetahui gambaran resiliensi murid yang belajar daring. Penelitian ini menggunakan pendekatan kualitatif dengan responden penelitian adalah murid SMP. Sebanyak 4 narasumber berpartisipasi dalam penelitian ini. Pengambilan data dilakukan melalui wawancara semi terstruktur secara online. Adapun panduan wawancara mengenai resiliensi dikembangkan dari teori resiliensi Reivich-Shatte. Hasil wawancara di analisa berdasarkan tema. Penelitian ini menggambarkan resiliensi yang dimiliki oleh siswa SMP yang melakukan pembelajaran daring ditunjukkan dengan 5 kemampuan dari 7 aspek resiliensi yaitu emotion regulation, impuls control, causal analysis, emphaty dan reaching-out dalam menjalani kegiatan belajar daring yang menantang. Namun demikian, 2 aspek lainnya yaitu realistic optisme dan self-efficacy kurang dimiliki oleh narasumber. Hasil penelitian ini memberikan informasi kepada guru di sekolah mengenai aspek diri murid apa saja yang perlu dipertahankan dan yang harus ditingkatkan agar menjadi lebih resilien ketika melakukan pembelajaran daring.